CRIMINALISTIC METHODS OF INVESTIGATING CRIMES, WHICH ARE RELATED TO CORRUPTION - Natalia Vladimirovna , Kymlyk (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
This paper examines the general concept of forensic crime investigation techniques, and especially the investigation of crimes related to corruption as one of the types of crimes in the area of performance. The basic building blocks of methods of investigating this type of criminal offenses described how forensic techniques of adaptation to the specific crimes related to corruption.